Potting in the pandemic: investigating pottery skill development and its wellbeing impacts in Covid-19 Britain - O'Brien, CRK (2023)
The Covid-19 lockdowns in Britain during 2020 and 2021 deprived people of access to studios and workshops in which we typically understand the learning and practising of skilled crafts to occur through working amongst others with materials. In response, people turned to online video tutorials, social media, printed materials, and pre-made kits, to learn at home outside of the physical and social structures offered by the classroom or studio. Conducting digital and sensory ethnographic research with a range of novice to professional potters in this context, this thesis aims to explore how individuals were using these resources to learn pottery skills and the impact this had on their subjective psychological wellbeing. Combining Material Engagement Theory (MET) with approaches from digital and sensory anthropology, this thesis argues for the central role of digital and terrestrial materiality in the wider ecologies through which these cognitive processes emerge. In doing so, this thesis seeks to address three research aims. First, to develop a theoretical understanding of how engagements with materials and tools, as experienced in relation to their digital and terrestrial materiality, shape and constitute our cognitive processes. Second, to contribute to the literature on craft and skill development, with a focus on pottery, to explore how learning occurred in this context, with attendance to the active role of materials in this. Third, to further inter-disciplinary collaboration on the topic of mental health, moving away from internalist views of cognition, to explore how engaging in pottery might impact subjective psychological wellbeing and how this relates to skill. Through developing this novel approach, this thesis contributes to the interdisciplinary discussion on skill development, craft, and wellbeing, as well as offering a theoretical framework for understanding the materiality of our multisensory and affective engagements with digital media in the wider learning ecologies that emerge in postdigital contexts.